1998
DOI: 10.1128/jcm.36.7.2073-2075.1998
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spontaneous Fluctuations of Viral Load in Untreated Patients with Chronic Hepatitis C by Two Standardized Quantitation Methods: Branched DNA and Amplicor Monitor

Abstract: Quantitation of hepatitis C virus (HCV) RNA in serum has been used to predict and monitor the efficacy of interferon therapy in chronic HCV infection. We prospectively studied the fluctuation of viremia by a longitudinal follow-up of HCV RNA levels for 2 months in six untreated patients. Spontaneous fluctuations of HCV RNA ranged from 2.8- to 5.7-fold with branched DNA assay and from 2.9- to 5.6-fold with Monitor. These large spontaneous fluctuations (up to 0.75 log), observed daily, weekly, and monthly, raise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Studies of natural fluctuations of HCV‐RNA load show conflicting results. In some studies, small fluctuations of HCV‐RNA levels were reported [9–11]; however, in other studies, a wide range of fluctuations was observed [12,13]. These conflicting results might be associated with a small number of subjects, short periods of follow‐up, differences of measurement methods, and lack of a standard to evaluate the fluctuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of natural fluctuations of HCV‐RNA load show conflicting results. In some studies, small fluctuations of HCV‐RNA levels were reported [9–11]; however, in other studies, a wide range of fluctuations was observed [12,13]. These conflicting results might be associated with a small number of subjects, short periods of follow‐up, differences of measurement methods, and lack of a standard to evaluate the fluctuation.…”
Section: Discussionmentioning
confidence: 99%
“…Single time‐point measurement may be sufficient according to some studies; which found that HCV‐RNA levels fluctuated within a small range [9–11]. However, in other studies, a wide range of fluctuations was observed [12,13]. The natural fluctuation of viral load without treatment is not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the value of monitoring serum HCV RNA during treatment as a predictor of response or non-response to antiviral therapy [Nguyen et al, 1996;Lam et al, 1997;Halfon et al, 1998;Neumann et al, 2000;Jessner et al, 2001Jessner et al, , 2002Zeuzem et al, 2001;Berg et al, 2003;Herrmann et al, 2003;Layden et al, 2003]. European and American Consensus Conferences recommended the use of the HCV RNA decline to manage the patients during treatment [EASL, 1999;National Institutes of Health Consensus Development Conference, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Sample processing, operator technique, type of quantitative assay used, assay platform and interfering substances (ie, endogenous and exogenous material found concomitantly within the specimen which may alter quantitative results) may each introduce variability and reduce precision in reported HCV RNA levels. Historically, interpretation and comparison of reported HCV RNA measurements in the published literature were hampered by the use of different assay technologies (reverse transcriptase polymerase chain reaction [RTPCR], branch DNA [bDNA] and nucleic acid sequencebased amplification [NASBA]), different reported units of measurement, problems with the determination of HCV RNA for nongenotype-1 isolates and periodic changes in the dynamic range of some assays (eg, Roche monitor version 2.0 [Roche Diagnostics, USA]) (11)(12)(13)(14)(15)(16)(17). Some of these difficulties have been resolved by the development of newer generation assays and the adoption of a universal unit of HCV RNA measurement (ie, IU/mL).…”
Section: Analytical Variables Influencing Quantitative Hcv Rna Measuresmentioning
confidence: 99%